Optimization of Waste Valve Load on Hydram Pumps to Support Food Self-Sufficiency in Remote Areas - Jumriadi, Jumriadi; Isnian, Sitti Nur (PT FORMOSA CENDEKIA GLOBAL, 2025)
The research aims to analyze the effect of waste valve loads on the performance of hydraulic ram pumps in supporting food self-sufficiency in areas with agricultural lands located at higher elevations than the water source, with limited access to energy resources. The method used is experimental and analyzed using mathematical equations based on hydraulic ram pump theory. The measured data include water discharge, flow velocity, and pump efficiency. The waste valve load masses used are 0.5 kg, 0.55 kg, 0.6 kg, 0.65 kg, 0.7 kg, and 0.75 kg. The results show that the waste valve load mass affects water discharge, flow velocity, and pump efficiency. The highest pump efficiency occurred at a valve load mass of 0.55 kg, reaching 40.86%, while the lowest efficiency occurred at a valve load mass of 0.7 kg, at 25.33%.